E-LKPD PENGEMBANGAN E-LKPD UNTUK MELENGKAPI MODUL MATA PELAJARAN PDTO KELAS X DI SMK AL-HIKMAH OGAN KOMERING ILIR TAHUN AJARAN 2020/2021: A. PENDAHULUAN B. METODE C. HASIL DAN PEMBAHASAN D. SIMPULAN E. DAFTAR PUSTAKA - Landung Subangkit (JURNAL VOKASI DEWANTARA (JVD), 2023)
This study aims to produce E-LKPD material for hand tools to complete the Productive Basic Automotive Engineering subject module for class X students and to find out E-LKPD material for hand tools to support student learning activities. This type of observation is a research and development (Research and Development). This type of development is learning that uses 4D research & development (define, design, develop, disseminate). The technique of collecting data is by using a questionnaire and observation. The analytical technique used is descriptive quantitative. From the type of research here is the learning media, namely e-lkpd Hand Tools for PDTO subjects. This development can be declared very good/very feasible to use based on the feasibility test by material experts as much as 91%, media experts by 72%, field test results by 90%, so that the overall average of the evaluations carried out by material examiners, media examiners, and field testers get a score of 84% for a maximum score of 4 then it is included in the "very feasible" category. This research produces e-LKPD Hand Tools for PDTO subjects. Very suitable for use in learning.